Brewster effect of super‐low altitude target above terrestrial environments using modified facet‐based weighted four‐path model. Issue 4 (5th February 2021) - Zou, Gao Xiang; Tong, Chuang Ming; Sun, Hua Long; Peng, Peng; Song, Tao
Abstract: A modified facet‐based weighted four‐path model is presented to analyze the Brewster effect of super‐low altitude target above terrestrial environments. In this approach, the facet‐based weighted four‐path model (FWFPM) is established to simulate the mutual interactions between the super‐low altitude target and terrestrial environment. Gauss antenna radiation pattern is introduced to modify the FWFPM. The hybrid PO‐MEC method is applied, where the physical optics (PO) is utilized to calculate the scattering field from each facet, and the method of equivalent currents (MEC) is used to compute the scattering field from the edge structure. The validation of the proposed method is verified by the example of a super‐low altitude missile model above a rough surface. The Brewster effect of a super‐low altitude aircraft above diverse terrestrial environments is studied. Moreover, the influences of relative permittivity, the roughness of environment, and the target' s height on Brewster angle have been analyzed in detail to provide some useful conclusions.